The Implementation of The Pjbl Method Assisted by Padlet on Environmental Pollution Material on Student Science Literature - Yuni Arfiani; Muriani Nur Hayati; Ikhza Khaerul Anwar (Universitas Negeri Yogyakarta, 2021)
The study aimed to 1) determine the effect of learning using the PjBL model assisted by Padlet on environmental pollution material on student literacy, and 2) find out the student responses toward the learning using the PjBL model assisted by Padlet on environmental pollution material on students scientific literacy. The research used a quasi-experimental method with a Pretest-Posttest control group design. The sample selection techniques used Purpose Sampling, both Experiment and control class. Data collection techniques were questionnaires, documentation, and tests. Data analysis used the Independent Sample T-Test and the coefficient of determination. The finding showed that the treatment of the research subject was the class. In the experimental class, the pretest score was 71.79 and the posttest score was 75.94. Meanwhile, in the control class, the pretest score was 60.27 and the posttest score was 66.53. The N-Gain value was 0.35 in the Experiment class and 0.31 in the control class, so it was in the medium category. In short, the implementation of the PjBl model assisted by Padlet on environmental pollution material affects students' scientific literacy by 4.6%.